Monetary and Macroprudential Policy Coordination Among Multiple Equilibria - Agur, Itai. (Washington, D.C. : International Monetary Fund, 2018)
The notion of a tradeoff between output and financial stabilization is based on monetary-macroprudential models with unique equilibria. Using a game theory setup, this paper shows that multiple equilibria lead to qualitatively different results. Monetary and macroprudential authorities have tools that impose externalities on each other's objectives. One of the tools (macroprudential) is coarse, while the other (monetary policy) is unconstrained. We find that this asymmetry always leads to multiple equilibria, and show that under economically relevant conditions the authorities prefer different equilibria. Giving the unconstrained authority a weight on "helping" the constrained authority ("leaning against the wind") now has unexpected effects. The relation between this weight and the difficulty of coordinating is hump-shaped, and therefore a small degree of leaning worsens outcomes on both authorities' objectives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Bank; First Mover; Monetary Policy; WP